Various Carbon Chain Containing Linkages Grafted Graphene with Silver Nanoparticles Electrocatalysts for Oxygen Reduction Reaction. Issue 1 (1st January 2015) - Lee, Kyungmi; Ahmed, Mohammad Shamsuddin; Jeon, Seungwon
Abstract : In this study, we have synthesized an efficient catalyst by various carbon chain containing linkers grafted graphene with silver nanoparticles (AgNPs)-decorated GO-S-(CH2 ) x -SH (where x = 2, 3, 4 and denoted as GO- Cx -Ag) for oxygen reduction reaction (ORR). The structural and morphological properties have investigated via several instrumental methods. Among those catalysts, the GO- C2 -Ag has showed an excellent electrocatalytic performance by cyclic voltammetry (CV) and hydrodynamic techniques for ORR in alkaline media. Hydrodynamic voltammetry reveals that the GO- C2 -Ag modified electrode has catalyzed effectively at higher potential. The overall electrocatalytic results showed that the GO- C2 -Ag has better activity toward ORR and demonstrated nearly four electron transfer pathway into H2 O due to much grafting of linker molecule and smaller size of AgNPs. The value of transferred electron number ( n ) and other kinetic parameters have demonstrated that the GO- C2 -Ag is highly facilitated than that of GO-Ag and other GO- Cx -Ag to electrocatalytic oxygen reduction.